2014
DOI: 10.15835/nsb649457
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Broadleaf Weeds Control with Selectivity of Post-Emergence Herbicides in Sugar Beet (<i>Beta vulgaris</i> L.)

Abstract: The reduction of herbicide applications is a main research priority in recent years. In order to study the effect of individual post-emergence application of sugar beet broad-leaf herbicides at four to six true-leaf stage of weeds, experiments were conducted during 2013. Treatments included untreated control and several rates of desmedipham + phenmedipham + ethofumesate, chloridazon and clopyralid on Portulaca oleracea, Solanum nigrum, Amaranthus retroflexus and Chenopodium album. A completely randomized layou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(25 reference statements)
1
2
0
Order By: Relevance
“…by 66.8 and 56.3%, respectively. These results are in good harmony with those obtained by (Chitband et al, 2014) who stated that desmedipham + phenmedipham + ethofumesate were more potent than that of chloridazon and clopyralid against Portulaca oleracea, Solanum nigrum, Amaranthus retroflexus and Chenopodium album. The same conclusion was mentioned by (Mahmoud and Soliman, 2012).…”
Section: Effect Of Weed Control Treatmentssupporting
confidence: 89%
See 1 more Smart Citation
“…by 66.8 and 56.3%, respectively. These results are in good harmony with those obtained by (Chitband et al, 2014) who stated that desmedipham + phenmedipham + ethofumesate were more potent than that of chloridazon and clopyralid against Portulaca oleracea, Solanum nigrum, Amaranthus retroflexus and Chenopodium album. The same conclusion was mentioned by (Mahmoud and Soliman, 2012).…”
Section: Effect Of Weed Control Treatmentssupporting
confidence: 89%
“…Mixtures of post-emergence herbicides have to be applied to control the wide range of weed species in sugar beet crop, (Scepanovic 2007, Deveikyte andSeibutis, 2006). Chitband et al (2014) found that desmedipham + phenmedipham + ethofumesate, tank mixtures for satisfactory weed control and reduction Portulaca oleracea, Solanum nigrum, Amaranthus retroflexus and Chenopodium album. The objectives of this study, to evaluate the integration between sugar beet cultivars and some readymade herbicides such as Goltix plus, Goltix, Cross, and/or Harness on weed control and sugar beet yields and its components.…”
Section: Introductionmentioning
confidence: 95%
“…ha -1 ) as compared to other herbicide combinations. Other studies also have reported that phenmedipham plus desmedipham plus ethofumesate was more effective for controlling weeds by applying in a mixture with metamitron than by applying alone phenmedipham plus desmedipham plus ethofumesate [54,55]. The combination of herbicides decreased sugar beet root yield as compared to the handweeded check (Control I).…”
Section: Combinations Of Phenmedipham Desmedipham Ethofumesate Metmentioning
confidence: 94%